What works in coach learning, how, and for whom? A grounded process of soccer coaches` professional learning - Stodter, A.; Cushion, C. J. (Qualitative Research in Sport, Exercise and Health, 2017)
Research into sport coaches` learning previously relied on descriptive learning histories and retrospective coach perceptions that revealed little detail about the processes and outcomes involved. More recent nuanced approaches have started to evidence the idea that coaches actively integrate multiple experiences as interconnected modes of learning, influenced by pre-existing biography. A learning theory specific to coaching that can explain how practitioners dynamically interact with learning environments is a necessary addition to advance understanding, inform professional development opportunities and move the field forward. This research aimed to address this gap by investigating the learning of 25 English youth soccer coaches. Longitudinal semi-structured interviews and video stimulated recall interviews were used to elicit knowledge use in practice, associated sources of learning, and moderating factors. Data were organised and analysed using techniques and principles of grounded theory. A substantive grounded theory is presented to explain the filter process whereby individuals adopted, adapted and rejected elements of their experiences, leading to uneven learning in apparently similar situations. The findings suggest that coaches actively constructed and experimented with knowledge for use in socially situated coaching practice, through double-loop individual and contextual level filters, and `reflective conversations`. Questions of `what works`, how and for whom in this context of coach learning are addressed for the first time. Elucidation of these processes can enhance professional learning and practice through advancing evidence based `theory in context.`